Preserving the Past, Embracing the Future: Co-Design Strategies for Achieving Harmony Between Heritage Sites and Accessibility Needs - Maryem Lakoud; Ernesto Morales; Alicia Ruiz-Rodrigo; Isabelle Feillou; Samuel Mathieu; Jonathan Riendeau; François Routhier (Heritage)
Canada’s heritage sites, while fewer in number compared to Europe, face significant challenges in accessibility due to strict preservation laws. Many were built before social inclusion became a priority, making them difficult to navigate for individuals with disabilities. For example, cobbled streets with uneven surfaces or significant level differences create obstacles for wheelchair users and others with mobility challenges. This qualitative action research aimed to develop guidelines for shared street designs and innovative solutions that balance heritage preservation with inclusive accessibility. The study involved go along interviews with 21 participants with disabilities in Quebec City’s Petit-Champlain and Place-Royale areas, as well as the Old-Seminary. Insights from these interviews informed a co-design methodology involving three sessions with participants with disabilities, family caregivers, and experts in accessibility and heritage. The co-design sessions generated practical solutions such as lift platforms, accessible signage, and guided handrails, addressing both outdoor and indoor accessibility barriers. For indoor spaces, solutions included integrating acoustic panels and foldable seating, while outdoor recommendations emphasized autonomous access solutions like non-slip coatings and accessible elevators for winter conditions. It was concluded that achieving a balance between preservation and accessibility requires collaboration among architects, designers, heritage experts, and individuals with disabilities. This research highlights the importance of co-design as a method to ensure heritage sites remain culturally significant and universally accessible.